Network Diffusion Algorithms and Simulators in IoT and Space IoT: A Systematic Review - Charbel Mattar; Jacques Bou Abdo; Jacques Demerjian; Abdallah Makhoul (Journal of Sensor and Actuator Networks)
Network diffusion algorithms and simulators play a critical role in understanding how information, data, and malware propagate across various network topologies in Internet of Things and Space IoT configurations. This paper conducts a systematic literature review (SLR) of the key diffusion algorithms and network simulators utilized in studies over the past decade. The review focuses on identifying the algorithms and simulators employed, their strengths and limitations, and how their performance is evaluated under different IoT network topologies. Common network simulators, such as NS-3, Cooja, and OMNeT++ are explored, highlighting their features, scalability, and suitability for different IoT network scenarios. Additionally, network diffusion algorithms, including epidemic, cascading, and threshold models, are analyzed in terms of their effectiveness, complexity, and applicability in IoT environments with diverse network topologies. This SLR aims to provide a comprehensive reference for researchers and practitioners when selecting appropriate tools and methods for simulating and analyzing network diffusion across IoT and Space IoT configurations.